Robust Genome Editing with Short Single-Stranded and Long, Partially Single-Stranded DNA Donors in Caenorhabditis elegans. Issue 3 (13th September 2018) - Dokshin, Gregoriy A; Ghanta, Krishna S; Piscopo, Katherine M; Mello, Craig C
Abstract: A robust genome editing pipeline is critical to the vitality of a modern genetic laboratory. Previous studies have shown that Cas9 ribonucleoprotein (RNP)-based editing can be highly effective in Caenorhabditis elegans, particularly... CRISPR-based genome editing using ribonucleoprotein complexes and synthetic single-stranded oligodeoxynucleotide (ssODN) donors can be highly effective. However, reproducibility can vary, and precise, targeted integration of longer constructs—such as green fluorescent protein tags remains challenging in many systems. Here, we describe a streamlined and optimized editing protocol for the nematode Caenorhabditis elegans . We demonstrate its efficacy, flexibility, and cost-effectiveness by affinity-tagging 14 Argonaute proteins in C. elegans using ssODN donors. In addition, we describe a novel PCR-based, partially single-stranded, "hybrid" donor design that yields high efficiency editing with large (kilobase-scale) constructs. We use these hybrid donors to introduce fluorescent protein tags into multiple loci, achieving editing efficiencies that approach those previously obtained only with much shorter ssODN donors. The principals and strategies described here are likely to translate to other systems, and should allow researchers to reproducibly and efficiently obtain both long and short precision genome edits.